Uczyć poetyk - dawnych i nowych! - Wysłouch, Seweryna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Poetics is of systemic nature and is dually dependent: on methodology (as it stems from methodological assumptions), and on literature (as it serves the purpose of analysing a literary work). Hence, when these two disciplines undergo transformations, poetics does too. Apart from the structural poetics which has now come in for a lot of criticism, one may also distinguish generative poetics (narratology) and cognitive poetics. Each of them has different aims and suggests their own and dissimilar research tools. Generative poetics postulates studying the mechanism of formation of the plot structures, whereas cognitive poetics aims at studying the perception of literature. The author of the article proposes “teaching poetics of both former and present times”, and check their usefulness in analysing literary works. She also postulates introducing cultural poetics which will serve the purpose of analysing texts which use various modes of expression.
Teach Poetics of Former and Present Times!
Keywords: poetyka; teoria literatury; budowa dzieła literackiego; poetyka generatywna; poetyka kognitywna